Drosophila PDZ-GEF, a Guanine Nucleotide Exchange Factor for Rap1 GTPase, Reveals a Novel Upstream Regulatory Mechanism in the Mitogen-Activated Protein Kinase Signaling Pathway - Lee, Jun Hee (American Society for Microbiology, 2002)
PDZ-GEF is a novel guanine nucleotide exchange factor for Rap1 GTPase. Here we isolated Drosophila melanogaster PDZ-GEF (dPDZ-GEF), which contains the all-conserved domains of mammalian and nematode PDZ-GEF including cyclic nucleotide monophosphate-binding, Ras exchange motif, PDZ, RA, and GEF domains. dPDZ-GEF loss-of-function mutants were defective in the development of various organs including eye, wing, and ovary. Many of these phenotypes are strikingly similar to the phenotype of the rolled mutant, implying that dPDZ-GEF functions upstream of the mitogen-activated protein (MAP) kinase pathway. Indeed, we found that dPDZ-GEF is specifically involved in photoreceptor cell differentiation, facilitating its neuronal fate via activation of the MAP kinase pathway. Rap1 was found to link dPDZ-GEF to the MAP kinase pathway; however, Ras was not involved in the regulation of the MAP kinase pathway by dPDZ-GEF and actually had an inhibitory function. The analyses of ovary development in dPDZ-GEF-deficient mutants also demonstrated another role of dPDZ-GEF independent of the MAP kinase signaling pathway. Collectively, our findings identify dPDZ-GEF as a novel upstream regulator of various morphogenetic pathways and demonstrate the presence of a novel, Ras-independent mechanism for activating the MAP kinase signaling pathway.